Identification of soybean genotypes adaptive and productive to acid soil agro-ecosystem - M. MUCHLISH ADIE; AYDA KRISNAWATI (Society for Indonesian Biodiversity, 2016)
Adie MM, Krisnawati A.2016. Identification of soybean genotypes adaptive and productive to acid soil agro-ecosystem.Biodiversitas 17:565-570. Optimalization of acidic land for soybean development can be performed through the provision of soybeanvariety adapted to low pH. A total of 13 soybean genotypes was identified for its performance on three acid soil sites in LampungProvince, Indonesia, from February to June 2015. Soybean variety adapted to acid soil (Tanggamus and Demas 1) were used as checkvarieties. The experiment was using Randomized Block Design, 15 traits and four replicates. The concentration of pH (H2O) in locationsL1, L2 and L3 were 5.87, 5.04, and 4.73, respectively. The average yield in L1, L2 and L3 were 1.96 t/ha, 2.17 t/ha, and 1.92 t/ha,respectively. This showed thatyielddecrease assoil pHvaluedecline. Genotype G4ABwas consistently produced highest yield at pH5.04 as well as at pH 4.73, hence the genotype G4AB was not only adaptive at low pH but also relatively productive. Based on yield inthree locations, G4AB categorized as less stable. On the contrary, genotypeG115H/Kaba//Kaba///Kaba-8-6 produced average yield of2.23 t/ha, and categorized as stablein three sites of acid soil. Soybean genotype adaptive to acid soil was characterized by its ability tomaintain the plant height,and followed by a high number of node per plant and pod per plant.